Pelatihan Konvensi Hak Anak untuk Mewujudkan Sekolah Ramah Anak dan Menguatkan Implementasi Merdeka Belajar di Sekolah Menengah Kejuruan - Senowarsito, Senowarsito; Werdiningsih, Yuli Kurniati; Suciati, Sri; Yulianti, Fitri (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Child-friendly school (CFS) has been interesting topic in years. But unfortunately, most of the schools that put this branding as friendly schools do not apply it properly. The CFS team from Universitas PGRI Semarang concerned on sharing information about the application of CFS on vocational school to the school’s team (stakeholders, teachers, education staffs, students, parents, and school committee) of Kartika Aqasa Bhakti Semarang aviation vocational school so they get the same perception on CFS. The school itself apply semi military activities in their daily activitieshe training was an implementation of the Convention on the Rights of the Child (CRC) as a reinforcement for the Independent Curriculum (Kurikulum Merdeka Belajar). The methods used are socialization, training, mentoring, monitoring, and evaluation. The results achieved were 90% of the school team had the same perception regarding the implementation of the children's rights convention and the SRA (Sekolah Ramah Anak, children-friendly school-CFS)  concept in schools, and there was an increase in the understanding and ability of the CFS Driving Team about the implementation of the children's rights convention and the implementation of CFS in schools by 95% and 90%.  This service activity shows that training can increase the awareness and ability of the CFS Team to implement CRC and CFS concepts in schools.